Telaah Tafsir Surah Al-Baqarah Ayat 129 dan 151 Menurut Para Mufassir Tentang Paradigma Pendidikan Islam - Dirja, Muldani Surya; Kanus, Oktari; Wibowo, Budi Santoso (An-Nuha, 2023)
This article aims to examine the main elements that must be the personality of a teacher by examining verses 129 and 151 in Surah Al-Baqarah. The method in this research is library research which is based on studies and also text analysis. This is done because the data sources used are in the form of literature data. It can be concluded that for Islamic educators in particular, they should be able to understand their role as educators. Understand the concept of the goals of Islamic education and also apply it in everyday life. By seeing the struggle of Rasulullah SAW, it is hoped that Muslim educators will be able to imitate his patience in educating his people. He educates his people from zero to experiencing significant changes. In addition, Muslim educators are also expected to be able to produce superior, intelligent, great, noble and dignified generations.